Mathematical Model of the Surveillance, Tracking and Fire Control System of the Short-Range ADGM System - Bogdan ZYGMUNT (Model matematyczny systemu obserwacji, śledzenia i kierowania ogniem PZRA krótkiego zasięgu, 2019)
The paper presents the development and simulation of a mathematical model of an automatic tracking and fire control system. The authors focused on very short-range air defense (VSHORAD) gun/missile systems.
Keywords: System kierowania ogniem w zestawie rakietowo-artyleryjskim